Bone Turnover Markers in Menopausal Women: A Comparative Study - Jaishankar, Thirunavukkarasu; Pattapu, Leela; Keerthika, Thota; Harshitha, TH; T, Saranya (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Menopause, characterized by the permanent cessation of menstrual cycles due to declining ovarian function, is diagnosed retrospectively after 12 months of amenorrhea. Postmenopausal women are at an increased risk of osteoporosis, a condition marked by reduced bone density and higher fracture risk. This study aims to assess markers of bone formation—serum total alkaline phosphatase (ALP) and bone-specific alkaline phosphatase (BSAP)—in postmenopausal women compared to premenopausal women. Additionally, urinary hydroxyproline, a marker of bone resorption, was measured and compared between the two groups. Methods: This case-control study included 20 healthy postmenopausal women (cases) and 26 healthy premenopausal women (controls). Following informed consent, blood samples were collected after an overnight fast to measure serum calcium, phosphorus, estradiol, total ALP, BSAP, and urinary hydroxyproline levels.Results: Postmenopausal women exhibited significantly higher serum total ALP, BSAP, and urinary hydroxyproline levels compared to premenopausal women (P < 0.001). Estradiol levels were significantly lower (P < 0.001), while serum phosphorus was higher in postmenopausal women (P = 0.017). Serum calcium levels showed no significant difference between the two groups (P = 0.911).Conclusion: The findings indicate that estrogen decline during menopause accelerates bone remodeling, as demonstrated by altered bone turnover markers, highlighting the increased risk of osteoporosis in postmenopausal women.